Application of the Ahsanul Qira'ah, Muroja'ah and Ziyadah (AHQMUZI) Method in Improving Students' Memorization Achievement at MDTA Al-Munawwarah Pamekasan - Wardatul Basyra; Muliatul Maghfiroh (al-Afkar, Journal For Islamic Studies, 2026)
In the daily learning process, several major problems arise. Teachers find that some students have difficulty maintaining previously memorized material, are inconsistent in adding new memorization content, and have not yet fully mastered proper reading techniques before proceeding to the next stage. This study aims to describe the implementation of the Ahsanul Qira’ah, Murojaah, and Ziyadah (AHQMUZI) method and its impact on the achievement of the students’ tahfidz program at MDTA Al-Munawwarah Pamekasan. This research employs a qualitative approach through observation, interviews, and documentation. The results show that the AHQMUZI method is a memorization activity that begins with students reciting verses in a tartil and correct manner using the Ahsanul Qira’ah method. This approach helps improve the quality of students’ recitation before memorization and provides positive effects and strong motivation on students’ memorization. Overall, the AHQMUZI method is effective in supporting the success of tahfidz learning in non-formal basic educational institutions.